UNITED STATES COUNTERTERRORISM POLICY EVALUATION - Anton Minardi (Journal of International Relations, 2022)
This article is summary from MA Project in International Relations Department European Unıversıty of Lefke, North Cyprus, 2016 whıch explained the counterterrorism policy of United States on ISIS and its impacts for further ISIS existence and regional peace. Base on the reasons that the appearance of ISIS seen as more of the results of obvious and severe conflicts in middle east partly in arab region. The conflicts seen have been expected by the interest of several countries. Eventually ISIS was existed as a state not only as a movement.U.S. counterterrorısm on ISIS had ımplemented amount of strategıes ıncludıng degraded ISIS’s capabılıty, shaped global coalıtıon to defeat ISIS, and mılıtary used wıth traınıng armed for Iraq army forces, Kurdı army, Arabıan army, moderate opposıtıton groups to Bassar.In congressional testimony and public statements early in 2015, U.S. civilian and military leaders described the ISIS as having assumed a defensive posture in Iraq and Syria in response to counteroffensives by coalition and local forces. U.S. Military General described the group as “losing this fight” and reported that anti-IS operations had killed more than 8,500 fighters, destroyed hundreds of vehicles and heavy weapons systems, and significantly degraded IS command and control capabilities.But ISIS is still exıst wıth theır weapons, moreover the presence of ISIS in Libya feared around the regions and near to Rome. The worst conditions not only happen in Syria, Iraq and Libya but the conflicts was also spreaded to many countries specially european countries. These countries are in dilemma positions. The other hand they intent to give the asylume to the refugees, but in the other hand they scaring from the exporting of ISIS’s ideologies more scares than economics crisis. The ISIS crisis was questioned obviously. How can the group such as ISIS can’t be destroyed in 3 years by U.S. attacks with global coalition power supporters. Whereas U.S. had defeated Afghanistan, Iraq, and Libya in several days, and set up the new goverments in each these countries.